Nexus between Working Capital Efficiency and Firm Risk-Taking: Evidence from MENA Countries - Alrahamneh, Luay Salem Mohammad; Chu, Ei-Yet; Hong, Meenchee (Journal of Entrepreneurship, Business and Economics; Vol 13 No 1 (2025), 2025)
This paper explores the interrelationship between the working capital management efficiency (WCME) and firm risk-taking (FRT) of 555 non-financial firms listed in the stock exchanges of key MENA countries, namely, Bahrain, Egypt, Jordan, Kuwait, Oman, Qatar, Saudi Arabia, and the U.A.E over the period 2016 to 2021. The study utilises net working capital as a measure of WCME, and capital expenditure ratio (CAPEX) as well as stock price movement (SPM) as proxies for FRT. The secondary annual quantitative data of 3,077 firm-year observations were collected from standards and poor’s global market intelligent database (SP, 2021). The study provides interesting perceptions. The coefficients of endogenous relationships between the WCME and the FRT measures are significant negative, indicating that MENA firms finance their investments in fixed capital through their working capital- a less costly internal source of financing- compared to external sources of financing. Further, MENA firms are a type of risk-averse firms by investing in low risk and return projects; and they adopt conservative working capital management and keep higher levels of their working capital. These insights assist corporate managers of firms in MENA countries in the adoption of efficient working capital practices to ensure liquidity and hinting at potential future growth prospects. Research Paper Keywords: Working Capital Management Efficiency, Firm Risk-taking, MENA Countries Reference to this paper should be made as follows: Alrahamneh, L.S.M., Chu, E.Y., & Hong, M. (2025). Nexus between Working Capital Efficiency and Firm Risk-Taking: Evidence from MENA Countries. Journal of Entrepreneurship, Business and Economics , 13 (1), 1–54.